Analisis Kausalitas Antara Pendidikan, Kemiskinan, dan PDRB Menggunakan Panel Vector Autoregression - Sisilia Jesika Pririzki; Ineu Sulitiana; Adriyansyah Adriyansyah (Euler : Jurnal Ilmiah Matematika, Sains dan Teknologi, 2023)
The condition of education in the Bangka Belitung Islands Province is still far from basic education, with the Average Years of Schooling (RLS) of 7.84 years. Apart from the education side, the number of existing poverty also tends to fluctuate every year. It is the same with the economic picture based on GRDP values which experience inequality between Regencies and Cities in the Bangka Belitung Islands Province. The purpose of this study is to determine the causal relationship between education, poverty, and GRDP. The approach method used is to use the Panel Vector Autoregression (PVAR) method by conducting a Granger causality test. The results of this study are that there is no causality relationship, but has a one-way relationship between poverty and education which has a probability value smaller than α of 5%, namely 0.0246. There is no causal relationship between education and GRDP with probability values of 0.1020 and 0.4706. There is a causal relationship between poverty and GRDP with a probability value for each variable 2x10^-9 and 8x10^-9.